Using organisational development and learning methods to develop resilience for sustainable futures with SMEs and micro businesses: The case of the "business alliance". Issue 2 (16th May 2016) - Gray, Dee; Jones, Katherine Fiona
Abstract : Purpose: – The purpose of this paper is to explore the potential of a collaborative organisational development and learning (OD/L) programme for small and medium-sized enterprise's (SME's) and micro businesses (MB) to contribute towards business resilience and sustainability. Design/methodology/approach: – This is an ethnographic case study that utilised an iterative interpretative approach to data collection and analysis, which was conducted around key OD/L interventions. Findings: – The findings demonstrate that the provision of an OD/L programme that focused on collaboration and learning, had both an immediate positive effect on business owners and long term effect in relation to business confidence, clarity, and action. Research limitations/implications: – The limitations of this study relate to the fact that the sample population is small so that the findings are not generalisable, and some of the challenges faced by SME business owners may be confined to socially deprived rural locations. Future research could focus on replicating the designed OD/L programme, or aspects of it, and a longitudinal study could be conducted over time. Practical implications: – The practical implications of this study are that it gives direction for those designing support for SME/MB's to include tried and proven OD/L interventions. Social implications: – The social implications include that by demonstrating targeted support to SME business owners in socially deprived areas, the potential for growth in terms of survival and flourishing are increased and economic regeneration is positively influenced. Originality/value: – There are few studies in this area, the OD/L programme highlights that collaboration, and sustainable actions to develop resilience, have a part to play in supporting the SME/MB population, and a contribution to make towards a more buoyant economy.